A dementia-friendly church: How can the African American church support families affected by dementia?. (February 2021) - Epps, Fayron; Heidbreder, Virginia; Alexander, Karah; Tomlinson, Audrey; Freeman, Valencia; Williams, Nancy
Dementia, including Alzheimer's disease, is affecting the African American community at alarming rates, as African Americans have a greater risk of dementia than other races. The African American church has traditionally been a safe haven where families go for support and healing. However, many churches are not equipped to support families living with dementia. The purpose of this study was to explore ways African American churches can be dementia-friendly to support families affected by dementia. A qualitative descriptive design was used to collect data from 12 African American community stakeholders. Participants were inclusive of caregivers, church leaders, community members, and service providers. During the semi-structured interviews, participants were asked to share characteristics of a dementia-friendly church. Thematic analysis was performed using data from interviews, researcher's journal, and field notes. Responses described a dementia-friendly church as (a) resourceful ; (b) welcoming and friendly ; (c) inclusive and comfortable ; (d) understanding and accepting ; and (e) c oncerned about personal well-being. This study has wide implications not only for African American churches and families, but also for families living with dementia outside of African American faith communities. These findings allow for faith leaders and churches to begin the process of becoming dementia-friendly, thus enabling congregations, communities, and persons with dementia to continue living in meaningful ways. In conclusion, churches are a source of religious support and provide access to resources for families in difficult times. Thus, it is imperative for African American churches to explore ways to best support and meet the needs of families living with dementia.